Behavioural response of Australian humpback whales to seismic surveys - Cato, D.; Noad, M.; Dunlop, R.; McCauley, R.; Salgado Kent, Chandra; Gales, N.; Kniest, E.; Noad, J.; Paton, D. (Acoustical Society of America, 2011)
The first of four major experiments in project behavioural response of australian humpback whales to seismic surveys (BRAHSS) was conducted on the east coast of Australia in September and October 2010. The project aims to understand how humpback whales respond to seismic surveys and to provide the information that will allow these surveys to be conducted efficiently with minimal impact on whales. It also aims to determine how the whales react to ramp up or soft start, and to assess how effective this is in mitigation. The 2010 experiment used a single air gun. Four air guns will be used in the next two experiments and a full seismic array in the final experiment in 2013. During the 2010 experiment, behavior and tracks of whales were recroded by four theodolite stations on elevated coastal positions and DTAGs used on some whales. Vocalizing whales were tracked with a wide base line hydrophone array. A further four acoustic recorders were used to measure propagation loss and to characterize the sound field throughout the area. A wide range of variables likely to affect whale response was measured. [Work sponsored by the JIP E&P Sound & Marine Life and Bureau of Ocean Energy Management, Regulation and Enforcement.]